(untitled) (Islamic Sciences Journal, 2023)
The research begins with the definition of Justice principle, which is about giving everyone’s rights and placing everything in its rightful position, appreciating each matter according what it is worth, and refrain from injustice, discrimination, and racism in managing affairs. In the first chapter, the research deals with the meaning of Justice in The Holly Quran, with mentioning its types, and followed by explaining the difference between justice and equity in Islamic law(Sharia) and laws. Then, in the second chapter, the research defines the implications of the principle of justice in administration and mentions practical instances in the Holy Quran as well as the Sunnah of the Prophet concerning this matter, as indicated that the Holy Quran commanded justice even with enemies, and thus it surpasses all human laws and systems in spreading justice and applying it in human society. In the third chapter, this paper further describes the constitutional and legal foundation of the principle of justice, where it encompasses the insistence of the Iraqi legislations concerning the embodiment of the constitutional laws, and its general principles of justice that the state follows. It also emphasized the principle of justice before the law, and this emphasis occurs in many constitutional provisions and clauses as well as laws in different forms. What is related to the conclusion, the reasercher presented the most important findings concluded by the research.